PENENTUAN KADAR RHODAMIN B DALAM KERUPUK MENGGUNAKAN METODE SPEKTROFOTOMETRI SINAR TAMPAK - Lutfia Wardani, Septiani
Rhodamine B is a dye of xanthenes group used to impart color in textile, paper, plastic, and paint. However, Rhodamin B is frequently misused as food colorant. The aim of this research was to obtain a method for determination of Rhodamine B in kerupuk by means of visible spectrophotometry applicable for routine analysis of Rhodamine B in kerupuk commercially available. Rhodamine B was extracted using solvent mixture consisting of 70% ethanol : 25% ammonia (98:2 v/v) from sample matrices. The analyte was subsequently adsorbed with fat-free wool fiber from sample extract followed by desorption of this analyte using solvent mixture consisting of methanol : 25% ammonia (60:40 v/v) to result in analyte solution. Absorbance of the analyte solution was then measured by visible spectrophotometrically at 547 nm. Analytical method was validated and determination of Rhodamine B in kerupuk sample comercially available was carried out. Measurements of Rhodamine B standard solution within range of 1.0 –3.5 ?g/mL resulted in a calibration curve of y = 0.2054 x + 0.0166, with correlation coefficient (r) of 0.999, process variation coefficient (Vx0) of 0.54%, limit of detection (LOD) of 0.04 ?g/mL, and limit of quantitation (LOQ) of 0.13 ?g/mL. Recovery of Rhodamine B in simulation samples at concentration levels of 2.0, 2.5, and 3.0 µg/mL were 103.95, 109.4, and 106.47%, respectively. Repeatability test of Rhodamine B standard solutions determination gave coefficient of variance (CV) of 0.52%, while that of simulation sample was 0.71%. Precision test of intra- and inter-day resulted in coefficient variation (CV) of 1.02 and 2.84% respectively. Based on overall results it was concluded that a valid visible spectrophotometric method for determination of Rhodamine B in kerupuk was successfully obtained which is applicable for routine determination of this analyte in kerupuk commercially available. Determination Rhodamine B in 41 kerupuk samples showed that no Rhodamine B was detected in 11 of the samples, while in 30 samples, Rhodamine B was detected, within a range of 10.4 –61.0 µg/g, with mean, modus, median, and concentration at 97.5% percentil of 26.5, 24.0, 25.7, and 57.5 µg/g.